Histopathological reporting of paediatric cutaneous vascular anomalies in relation to proposed multidisciplinary classification system. Issue 12 (2nd June 2006) - Al-Adnani, M; Williams, S; Rampling, D; Ashworth, M; Malone, M; Sebire, N J
Abstract : Background: The terminology applied to vascular anomalies has been variable in previously published literature making interpretation suboptimal. The International Society for the Study of Vascular Anomalies (ISSVA) has proposed a revised classification based on clinical features and histopathological findings. This classification is increasingly being accepted as clinically useful and a platform for future studies. Aims: To examine the extent to which the ISSVA classification can be practically applied to diagnostic histopathological specimens. Methods: Cutaneous vascular lesions received in a single paediatric pathology unit during a 2-year period (2004–5) were reviewed, including glucose transporter protein 1 (GLUT1) immunostaining where required, and lesions were reclassified according to the ISSVA classification. Results: 144 specimens were identified. Appropriate full clinical information was provided in only 17% of cases at submission. Infantile haemangiomas comprised 46% of cases, 18% of which were regressive type, initially inaccurately identified as vascular malformations before GLUT1 immunostaining. 30% of lymphatic malformations and all lymphovenous malformations were previously classified as vascular malformations, not otherwise specified. Conclusions: The ISSVA classification of vascular anomalies provides a useful framework for histopathologists to classify vascular anomalies. However, meaningful and appropriate use of such a system is dependent on the adequacy of clinical information provided and routine use of immunohistochemical markers.